Comparison of the efficacy of artesunate-amodiaquine with quinine-clindamycin for treatment of uncomplicated falciparum malaria in children - Purnama Fitri; Armila Armila; Munar Lubis; Syahril Pasaribu; Chairuddin P. Lubis (Indonesian Pediatric Society, 2009)
Background Drug-resistant Plasmodium falciparum malaria is amajor contributor to increasing malaria-related morbidity andmortality. Artesunate-amodiaquine is a potential combinationtherapy that shows improved treatment efficacy. Clindamycin incombination with quinine is also a safe and effective treatmentfor multidrug-resistant P. falciparum malaria.Objectives To compare the efficacy of artesunate-amodiaquine andquinine-clindamycin combination therapies for the treatment ofuncomplicated falciparum malaria.Methods This randomized open label trial in 23 2 children agedbetween one month and 18 years old took place in MandailingNatal, North Sumatra, from August to September 2006. The AAgroup received a 3-day oral course of artesunate (4 mg/kg BWonce a day) plus amodiaquine (10 mg/kg BW once a day). TheQC group received a 3-day course of clindamycin (5 mg of base/kgBW twice a day) plus a 7-day course of quinine (10 mg of salt/kgBW orally for the first four days, then 5 mg of quinine salt/kg BWfor the next three days). We performed thin and thick peripheralblood smears on days 0, 2, 7, and 28.Results A total of 232 eligible children were enrolled but only22 7 completed the study (114 in group AA, 113 in group QC).The cure rates were lOOo/o in both groups by the second day, andthere was no recrudescence in either group. We found more sideeffects in AA group compared with in QC group, i.e., headacheand vomiting.Conclusion Artesunate-amodiaquine and quinine-clindamycincombinations showed similar efficacy for the treatment of uncomplicatedP. falciparum.